2021
DOI: 10.3390/s21020564
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluations with 2d Electrical Resistance Tomography in the Low-Conductivity Solutions Using 3d-Printed Phantoms and Sucrose Crystal Agglomerate Assessments

Abstract: Crystallization is a significant procedure in the manufacturing of many pharmaceutical and solid food products. In-situ electrical resistance tomography (ERT) is a novel process analytical tool (PAT) to provide a cheap and quick way to test, visualize, and evaluate the progress of crystallization processes. In this work, the spatial accuracy of the nonconductive phantoms in low-conductivity solutions was evaluated. Gauss–Newton, linear back projection, and iterative total variation reconstruction algorithms we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Effective use of such images is critically reliant on the choice of reconstruction parameters and the flexibility to change them quickly. We systematically studied such parameters for analyzing non-conductive materials in the low conducting media [25]. For cylindrical chemical batch crystallization reactors, a conventional parameterization approach relies on testing and comparing the number of iterations, finite element model mesh structure, hyperparameter values, and tolerances, using simulations and phantoms.…”
Section: Development Of the Software Ert-vismentioning
confidence: 99%
See 1 more Smart Citation
“…Effective use of such images is critically reliant on the choice of reconstruction parameters and the flexibility to change them quickly. We systematically studied such parameters for analyzing non-conductive materials in the low conducting media [25]. For cylindrical chemical batch crystallization reactors, a conventional parameterization approach relies on testing and comparing the number of iterations, finite element model mesh structure, hyperparameter values, and tolerances, using simulations and phantoms.…”
Section: Development Of the Software Ert-vismentioning
confidence: 99%
“…The final results determining accurate yield estimation and solid concentration distributions within the region of interest can be affected by variation in the parameters for image reconstruction or image segmentation. The quantitative evaluation of the crystallization progress and the factors affecting crystallization monitoring using ERT have been discussed extensively [24,25]. It was shown that multiple factors such as sensor size, reconstruction technique, conductivity of the solution under evaluation, elements in the Finite Element Model (FEM) mesh, and the image processing method utilized all affected the quantitative evaluation of the non-conductive regions.…”
Section: Introductionmentioning
confidence: 99%
“…Both speed and spatial resolution are important to capture the relevant dynamics of the separation inside ISS in real time. Previous works based on the correction of the lightphase core size measured by the sensor via calibration against a camera were successful in increasing the accuracy of the ERT system for non-iterative schemes [30,31], and approaches relying on artificial intelligence and machine learning are also present in literature [32]. However, there is still a mismatch between the flow time scales and the temporal resolution of the ERT with the correction.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical resistance tomography (ERT) is one of the fast-evolving tomographic modalities used to characterize a process through quantifying the electrical field of the medium. The fast growth of ERT is mostly due to the economic aspects, the relative simplicity of implementation, and the potential for sub-millisecond temporal resolution [16]. On the other hand, among the main disadvantages is the data acquisition rate, which affects the image reconstruction time; noise generation is highly correlated to measurement speed, therefore, undesirably impacting the image quality [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, among the main disadvantages is the data acquisition rate, which affects the image reconstruction time; noise generation is highly correlated to measurement speed, therefore, undesirably impacting the image quality [17]. Furthermore, the inherent nonlinearity of both the conductivity measurement and the inverse algorithms limits the spatial resolution of the electrical tomography technique to approximately 2-5% of the reactor diameter [13,16].…”
Section: Introductionmentioning
confidence: 99%